THE INFLUENCE OF ROLE CONFLICT, STRESS AND WORK ENVIRONMENT ON PERFORMANCE OF TEACHERS - Sian Harsep Logitapraja; Imam Suroso; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2019)
Employee performance is one of the benchmarks of success of an organization, whether it is good or not. So does that happen in school which is a company engaged in the field. For that, there is a need to research to find out what factors affected it. This research aims to find out if there is a conflict between the role of influence, stress, and work environment against performance of the teacher in SMK N IU Singojuruh, and became the object of this research that is all teachers teaching in SMK N IU SingojuruhBanyuwangi. Using Multiple regression analysis using SPSS software help.The results of this study demonstrate a significant influence between the role conflict, stress, and work environment against performance of the teacher in SMK N IU SingojuruhBanyuwangi simultaneously as well as partial in each from. In addition, in this study also noted that the working environment variable is the most dominant factor affecting performance.